Strategies to improve medication adherence in kidney transplant recipients: Addressing education and pill burden - Souza, Ana Carolina Brecher de; Menezes, João Daniel de Souza; Silva, Matheus Querino da; Freitas, Camila Borge de; Single, Luísa Carneiro; Lima, Bárbara Beraldo de; Santos, Emerson Roberto dos; Ribeiro, Renato Mendonça; Parro, Maria Claudia; Caldas, Heloisa Cristina; Lima, Alba Regina de Abreu; Spessoto, Luís Cesar Fava; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Adherence to immunosuppressive therapy is crucial for the success of kidney transplantation. This study aimed to evaluate medication adherence among kidney transplant recipients (KTRs) and identify factors associated with non-adherence. Methods: A cross-sectional study was conducted with 100 KTRs from a single transplant center. Adherence was assessed using the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS). Sociodemographic and clinical data were collected through interviews and medical records. Logistic regression analysis was performed to identify factors associated with non-adherence. Results: The prevalence of non-adherence was 65%. Delayed medication intake (≥2 hours) was reported by 36% of KTRs. Lower education levels were associated with a higher risk of delayed medication intake (OR=3.14; 95%CI: 1.28-7.72; p=0.012). A higher number of pills per dose was associated with a higher risk of non-adherence (OR=1.54; 95%CI: 1.03-2.30; p=0.036). Conclusions: Non-adherence to immunosuppressive therapy was common among KTRs. Lower education levels and a higher number of pills per dose were associated with non-adherence. Interventions targeting these factors, such as patient education and simplification of medication regimens, may improve adherence and transplant outcomes.